Glutathione S‐transferase (GST) genes and their function associated with pyrethroid resistance in the malaria vector Anopheles sinensis. Issue 10 (24th June 2022) - Tao, Fei; Si, Feng‐Ling; Hong, Rui; He, Xiu; Li, Xiang‐Ying; Qiao, Liang; He, Zheng‐Bo; Yan, Zhen‐Tian; He, Shu‐Lin; Chen, Bin
Abstract: BACKGROUND: Glutathione S ‐transferases (GSTs), a multifunctional protein family, are involved in insecticide resistance. However, a systematic analysis of GSTs in Anopheles sinensis, an important vector for malaria transmission, is lacking. In this study, we investigated the diversity and characteristics of GST genes, and analyzed their expression patterns and functions associated with insecticide resistance in this species. RESULTS: We identified 32 putative cytosolic and three putative microsomal GST genes in the An. sinensis genome. Transcriptome analysis showed that GSTs were highly expressed in larvae, and mainly expressed in the antennae, midgut and Malpighian tubules of adults. In addition, we found that GSTd2 and GSTe2 were significantly upregulated in four An. sinensis pyrethroid‐resistant field populations. Furthermore, silencing of GSTd2 and GSTe2 significantly increased the susceptibility of An. sinensis to deltamethrin, and recombinant GSTd2 and GSTe2 exhibited high enzymatic activity in the metabolism of 1‐chloro‐2, 4‐dinitrobenzene and dichlorodiphenyltrichloroethane (DDT). CONCLUSION: These results showed that GSTs are involved in the development of insecticide resistance in An. sinensis through transcriptional overexpression and enzymatic metabolization, facilitating our understanding of insecticide resistance in insects. © 2022 Society of Chemical Industry. Abstract : This study investigated the diversity and characteristics of GST genes, and their expression, function and enzyme activity associated with insecticide resistance in the malaria vector Anopheles sinensis .